Organisational Learning and Perceived Employability: A Model-Based Approach - Sylwia WISNIEWSKA; Kamil WISNIEWSKI; Robert SZYDŁO (Communications of International Proceedings, 2021)
Nowadays, the evolving labour market determines increased job insecurity and the growing importance of the employability of workers. Furthermore, the current market conditions imply a requirement for continuous learning and the everlasting development of competencies as the foundation for increasing one’s employability in the modern labour market. Therefore, the aim of the article is to explore the relationship between organisational learning solutions at the organisational level and perceived employability in the modern labour market, according to the opinions of the workers surveyed. This article reviews the current literature on organisational learning as well as perceived employability. Further, it analyses the results of own empirical research. The results are intended to stimulate and improve organisational learning processes to contribute to the development of the employability of workers in organisations. Within the exploratory approach, organisational learning solutions applied at the organisational level and perceived employability of workers were analysed using various tools, including general descriptive statistics, Shapiro-Wilk, Kruskal-Wallis H and Mann-Whitney U tests as well as Spearman’s Rho. The research confirmed that selected organisational learning solutions at the organisational level is positively correlated with perceived employability of workers.
Keywords: Perceived Employability; Organisational Learning; Labour Market.